Ananthakrishnana syn.n. of Haplothrips, with redescription of H. euphorbiae adult and larva (Thysanoptera) - Rousse, Pascal; Reynaud, Philippe (Zootaxa, 2025)
The generic name Ananthakrishnana is newly synonymised with Haplothrips, because each of the diagnostic character states occurs in other species of Haplothrips. The type species, Haplothrips euphorbiae comb.rev., is redescribed from both sexes and larvae and newly recorded from Reunion Island.